1978
DOI: 10.1017/s0043174500064833
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Microbial Degradation of14C-Glyphosate to14CO2in Soil

Abstract: 14C-glyphosate [N-(phosphonomethyl)glycine] degradation to14CO2was examined in a Spinks sandy loam, Collamer silt loam, and a Norfolk loamy sand. After 32 days, 40, 9.5, and 3% of the14C-glyphosate was recovered as14CO2in the three soils, respectively. The degradation was primarily microbial. Phosphate additions stimulated14C-glyphosate degradation to a limited extent in the Collamer silt loam but not in the Norfolk loamy sand. Additions of Fe+++and Al+++ions reduced degradation in the Spinks sandy loam. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 7 publications
4
24
0
3
Order By: Relevance
“…Normalmente, é observada uma taxa de decomposição inicialmente rápida, seguida por prolongada e lenta decomposição (Moshier & Penner, 1978). Esse comportamento reflete a facilidade com que a molécula é metabolizada pela microbiota do solo (Torstensson & Aamisepp, 1977;Dick & Quinn, 1995).…”
Section: Introductionunclassified
“…Normalmente, é observada uma taxa de decomposição inicialmente rápida, seguida por prolongada e lenta decomposição (Moshier & Penner, 1978). Esse comportamento reflete a facilidade com que a molécula é metabolizada pela microbiota do solo (Torstensson & Aamisepp, 1977;Dick & Quinn, 1995).…”
Section: Introductionunclassified
“…Sandy loam and clay has the strongest adsorption capacity for sulcotrione, followed by sandy clay and sandy soil. After adsorption by soil, sulcotrione is gradually released and does not disappear easily [17]. The sulcotrione soil residual level is affected by many factors.…”
Section: Discussionmentioning
confidence: 99%
“…Rice Forest Grass (1977) and Moshier & Penner (1978) found that 28 days were required to degrade 45% to 48% of the original glyphosate in the soil.…”
mentioning
confidence: 99%